Per-Flow Routing with QoS Support to Enhance Multimedia Delivery in OpenFlow SDN - Diorio, Rafael Fernando; Timóteo, Varese Salvador (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2016)
In this paper, we present the results obtained trough a per-flow routing resource with Quality of Service (QoS) support, provided by a multimedia gateway, to enhance multimedia delivery in OpenFlow Software-Defined Networks (SDN). We use the multimedia gateway to identify and classify multiple multimedia traffic flows on the network and to forward each traffic flow to the destination system according to specific flow rules, with different configurations of bandwidth allocation and priority of transmissions. In the SDN environment, the multimedia gateway acts as complementary component of the OpenFlow controller and as a network gateway of the endsystems. The interactions with the OpenFlow controller occur through a RESTful API, as an extension to the OpenFlow controller API Northbound. Through these interactions, with global information of the network, multimedia traffic flows can be routed and delivered differently from the other flows. These features are important to improve the multimedia distribution and to increase the user-perceived Quality of Experience (QoE).